Conversion Of A Tailing Impoundment To A Freshwater Reservoir, The Eagle Park Reservoir Project, Climax Mine, Colorado - B. R. Romig; J. L. Cupp; R. C. Ford (Society for Mining, Metallurgy & Exploration, 1999)
The Climax Molybdenum Mine, located near Leadville, Colorado, is the site of a lengthy mining history spanning more than 80 years. In the 1960’s, extraction of molybdenum from oxide ore located adjacent to the massive molybdenite sulfide deposit resulted in the construction of an earthen core dam to impound fine-grained oxide tailing in the Eagle River Valley. Through recognized value of water storage and reclamation opportunities, a tailing removal project was initiated in 1993 to convert the impoundment facilities to a post-mining beneficial land use of developed water resources. An evaluation of the effect residual materials and lake dynamics would have on in-stream water quality was performed. Eagle Park Reservoir stands as a model for future reclamation efforts that involve water delivery to highly sensitive receiving waters. This paper provides a case study on project development, the evolution of water quality assessment, and the regulatory framework that contributed to this project’s success.